(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article summarizes the history of the introduction and formation of variety art in Uzbekistan, as well as the historical activities of its prominent representatives. Moreover, facts related to the repertoire of outstanding figures in Uzbek variety art have been analyzed.